Estudio de Babesiosis spp en perros en condición de calle - González Aguirre, Carlos Washington (2023)
In this research case on canine babesiosis and its impact on street dogs, several relevant findings have been identified. Canine babesiosis has been found to affect both street animals and domestic dogs that come into contact with ticks, which act as vectors of the disease. Furthermore, it has been found that humans can also be affected by infection through tick bites. The importance of carrying out larger studies at the national level to obtain geographic information on the location of the animals and the incidence of the disease is highlighted. The implementation of vector control campaigns is also suggested, such as the sterilization of dogs in street situations, to reduce the reproduction and spread of the disease. The study's conclusions indicate the existence of various types of Babesia canis affecting dogs, which requires a deeper understanding of the symptoms of each variant and the implementation of appropriate diagnosis and treatment plans. The importance of recognizing the clinical signs of babesiosis, such as fever, lethargy, jaundice, kidney damage, and coagulation problems, is stressed in order to provide appropriate treatment.